Evaluation of Human Factors for the Next-Generation Displays: A Review of Subjective and Objective Measurement Methods - 문성철; 박민철 (대한인간공학회, 2013)
Objective: This study aimed to investigate important human factors that should be considered when developing ultra-high definition TVs by reviewing measurement methods and main characteristics of ultra-high definition displays. Background:Although much attention has been paid to high-definition displays, there have been few studies for systematically evaluating human factors. Method: In order to determine human factors to be considered in developing human-friendly displays, we reviewed subjective and objective measurement methods to figure out the current limitations and establish a guideline for developing human-centered ultra-high definition TVs. In doing so, pros and cons of both subjective and objective measurement methods for assessing humans factors were discussed and specific aspects of ultra-high definition displays were also investigated in the literature. Results: Hazardous effects such as visually-induced motion sickness, visual fatigue, and mental fatigue in the brain caused by undesirable TV viewing are induced by not only temporal decay of visual function but also cognitive load in processing sophisticated external information. There has been a growing evidence that individual differences in visual and cognitive ability to process external information can make contrary responses after exposing to the same viewing situation. A wide vision, ultra-high definition TVs provide, can has positive and negative influences on viewers depending on their individual characteristics. Conclusion: Integrated measurement methods capable of considering individual differences in human visual system are required to clearly determine potential effects of super-high vision displays with a wide view on humans. All of brainwaves, autonomic responses, eye functions, and psychological responses should be simultaneously examined and correlated. Application: The results obtained in this review are expected to be a guideline for determining optimized viewing factors of ultra-high definition displays and accelerating successful penetration of the next-generation displays into our daily life.